All-polyethylene composites reinforced via extended-chain UHMWPE nanostructure formation during melt processing - Zhong, Fan; Enders, Markus (Polymer, 2018)
Nanophase separation during injection molding of high density polyethylene (HDPE) together with polyethylene reactor blend (RB) additives that have ultrabroad bimodal molar mass distribution and a high content of ultrahigh molar mass polyethylene (UHMWPE), produces thermoplastic all-polyethylene composites reinforced with extended-chain UHMWPE nanostructures formed in situ. Neither alien fibers, inorganic fillers, hazardous nanoparticles nor modified single- and multi-step molding processes are required to convert HDPE into higher performance engineering plastics. The RB40 additive is readily tailored by ethylene polymerization on silica-supported chromium two-site catalysts and contains 40wt% UHMWPE (Mw=1.5×106g∙mol−1) dispersed in 50wt% HDPE wax (Mw=1.1×103g∙mol−1). The presence of disentangled nanophase-separated UHMWPE together with HDPE wax serving as a processing aid enables injection molding of all-PE composites with high UHMWPE content of up to 24wt% without changing processing parameters typical for HDPE. As verified by both scanning electron microscopic analyses of samples etched with hot xylene and thermal analysis, the HDPE matrix is efficiently reinforced by in situ formed polyethylene shish-kebab fibers where flow-induced crystallization yields extended-chain UHMWPE nanostructures as shish nucleating the crystallization of HDPE kebab. For the first time, by etching quenched samples, it was possible to completely suppress kebab formation and to image in situ extended-chain UHMWPE shish with an average diameter of 80nm. Upon increasing the UHMPE content the average total diameter of shish-kebab fiber-like structures drastically decreases from micron to nanometer range, forming non-woven-like architectures. This self-reinforcement simultaneously improves toughness, stiffness and strength parameters unparalleled by conventional melt-blending HDPE with micron-sized UHMWPE and HDPE wax. Compared to HDPE, the addition of 60wt% RB40 increases the Young's modulus to 4.2GPa, tensile strength to 160MPa and impact strength to 20kJ/m2. This sustainable route to self-reinforced all-PE composite composites preserves the high energy, resource, cost and eco-efficiencies typical for pure hydrocarbon resins. Here, we examine the impact of RB40 addition on in situ nanostructure formation and its correlation with thermal and mechanical properties of all-PE composites.
Gesehen am 01.04.2020